2008
DOI: 10.1111/j.1743-6109.2007.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Prior to First Drug Use Among Former Drug Addicts and Its Possible Causal Meaning on Drug Addiction: Preliminary Results

Abstract: Introduction Adolescence is one of the periods in which the risk of initial use of drugs is high. Among the reasons leading to first drug use (FDU), sexual disorders have so far been poorly investigated. Aim To evaluate the prevalence of premature ejaculation, erectile dysfunction, and low sexual desire in former drug addicts in the period prior to FDU; whether or not the former drug addicts claimed that sexual dysfunctions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
1
24
0
1
Order By: Relevance
“…Adolescence is at high risk of initial use of drugs. La Pera et al 5 showed that 71% of drug addiction might be because of the presence of one or more sexual dysfunctions (ED, premature ejaculation, low desire, alone or in combination), whereas only 29% of his series did not report any sexual problem. Among those with normal sexual function, only few stated that sexual dysfunctions had influenced their decision; on the contrary, in sexual dysfunction group, one out of three confirmed that the beginning of the assumption of drugs was depending on their sexual disorders, primarily premature ejaculation.…”
Section: Endothelial Dysfunction In Erectile Dysfunction a Aversa Et Almentioning
confidence: 97%
See 1 more Smart Citation
“…Adolescence is at high risk of initial use of drugs. La Pera et al 5 showed that 71% of drug addiction might be because of the presence of one or more sexual dysfunctions (ED, premature ejaculation, low desire, alone or in combination), whereas only 29% of his series did not report any sexual problem. Among those with normal sexual function, only few stated that sexual dysfunctions had influenced their decision; on the contrary, in sexual dysfunction group, one out of three confirmed that the beginning of the assumption of drugs was depending on their sexual disorders, primarily premature ejaculation.…”
Section: Endothelial Dysfunction In Erectile Dysfunction a Aversa Et Almentioning
confidence: 97%
“…It has been suggested that in young men below 30 years of age, the vascular origin of ED can be a false positive of duplex ultrasound procedure mainly because of the presence of an adrenergic overtone during the office setting, 3 but such data have been disregarded. 4 More notably, in this age range, cannabis use is highly prevalent (up to 80%) and even if the majority of drug users report a stimulation of sexual desire and improvement in sexual performance, 5 the real effects of cannabis use on vascular penile function appears to be poorly investigated. Animal studies have not underlined any significant modification in sexual activity, which would have led to the exclusion of any 'aphrodisiac' effect of this recreational drug.…”
Section: Introductionmentioning
confidence: 99%
“…These benefits sometime cause a person to start using drugs. But as it was mentioned before, as drug use continues, the user gradually develops an addiction, and builds up a tolerance to the drug, and as result, some problems are created in the dopamine center of the brain, and this leads to problems in sexual desire (National Drug Research Institute) [9]. Glutamate is another neurotransmitter that affects the pleasure circuit of the brain and learning ability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that using low doses of drugs for a short period of time may improve some aspects of sexual functioning [3][4][5][6][7][8]. These benefits sometimes cause a person to start using drugs [9]. Drug users gradually increase the amount and duration of their use, but the benefits are short-lived.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors wonder if a previous clinical condition won't be behind this experience and have a stronger influence than the drug use contingences (La Pera, et al, 2008;Palha & Esteves, 2002). More recently, investigators try to understand to which point the drug use/abuse and sexuality associations are accidentals or the result of an intentional substance use in order to achieve some sexual goals (Bellis et al, 2008;Rawson et al,2002).…”
mentioning
confidence: 99%